Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd000215.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintics for people with neurocysticercosis

Abstract: In patients with viable lesions, evidence from trials of adults suggests albendazole may reduce the number of lesions. In trials of non-viable lesions, seizure recurrence was substantially lower with albendazole, which is counter-intuitive. It may be that steroids influence headache during treatment, but further research is needed to test this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…Previous meta-analyses [ 9 , 10 , 13 ] reported that anthelmintic therapy with albendazole improved the seizure-free rate and hastened the resolution of the granuloma. However, these analyses combined clinical trials with different comparison groups (anthelmintics versus conservative treatment, anthelmintics versus corticosteroids, combination of anthelmintics and corticosteroids versus conservative treatment, and combination of anthelmintics and corticosteroids versus corticosteroids) making it impossible to determine the efficacy of anthelmintics itself and of the combination therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous meta-analyses [ 9 , 10 , 13 ] reported that anthelmintic therapy with albendazole improved the seizure-free rate and hastened the resolution of the granuloma. However, these analyses combined clinical trials with different comparison groups (anthelmintics versus conservative treatment, anthelmintics versus corticosteroids, combination of anthelmintics and corticosteroids versus conservative treatment, and combination of anthelmintics and corticosteroids versus corticosteroids) making it impossible to determine the efficacy of anthelmintics itself and of the combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment might be different for patients with live and degenerative/dead parasite. While there is sufficient information in support of the use of the combination of anthelmintics and corticosteroids in patients with viable cystic parenchymal NCC [ 6 10 ], the treatment of SCG has not been optimally defined [ 11 ]. Besides, the recent American Academy of Neurology (AAN) evidence-based guideline on NCC didn’t address management issues of different types of lesion independently [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Toda esta complejidad, asociada a una discusión no resuelta sobre la efectividad de los cesticidas y el rol de los corticoides, explica que bajo un común diagnóstico exista una diversidad en las conductas de tratamiento [4][5][6] . Los pacientes de esta serie permiten ilustrar la diversidad comentada.…”
Section: Sr Editorunclassified
“…More than 25 years of experience has accumulated since the advent of cysticidals [12], and along this time countless studies have been performed with albendazole and with praziquantel and have provided answers to these three main questions: 1) adverse inflammatory reactions secondary to the drug-induced destruction of parasites are effectively controlled by a brief course of steroid therapy; 2) long-term studies have shown that the opportune elimination of parasites is frequently accompanied by improvement of the specific neurologic dysfunctions caused by the parasites [1, 29,32,33]; and, more important, 3) it seems logical to consider that in NCC, as in any other infectious disease in which an effective and convenient therapy exists (in economical cost, drug toxicity, and length of therapy), there is no reason to leave the disease to follow its natural course, in patients with mild forms of the disease, when an effective and safe cure can be achieved [6••, 34]. Currently, most experts agree with the use of antihelmintic therapy when viable cysticerci are encountered [6••, 33].…”
Section: Treatmentmentioning
confidence: 99%